МЕТОДИ КЕРУВАННЯ ГЕНЕРАТОРАМИ НА БАЗІ МАШИНИ ПОДВІЙНОГО ЖИВЛЕННЯ У МІКРОМЕРЕЖАХ: ОГЛЯД ТА ПЕРСПЕКТИВИ РОЗВИТКУ - Швець, В.С. (Інститут електродинаміки Національної академії наук України, 2026)
The paper presents a review of current research and technical solutions related to the application of doubly fed induction generators (DFIG) in microgrids to improve power quality. The operational features of DFIG under unbalanced voltage conditions, arising from uneven load distribution, varying line impedances, and the influence of nonlinear consumers, are examined. The main control approaches are analysed, including vector control, direct power control, and intelligent methods such as fuzzy logic and hybrid algorithms. The advantages and limitations of each method are identified in terms of torque ripple compensation efficiency, reduction of harmonic distortions, and enhancement of system stability. Prospects for the development of DFIG control technologies are outlined in the context of integrating renewable energy sources into microgrids and ensuring power supply stability. Ref. 16, fig. 6.